Distinct CCR7 glycosylation pattern shapes receptor signaling and endocytosis to modulate chemotactic responses. Issue 6 (27th January 2016) - Hauser, Mark A; Kindinger, Ilona; Laufer, Julia M; Späte, Anne-Katrin; Bucher, Delia; Vanes, Sarah L; Krueger, Wolfgang A; Wittmann, Valentin; Legler, Daniel F
Abstract : N-glycosylation of CCR7 is a determinant of CCR7 signaling and T cell migratory capacity which is modulated by glycosidases released from DCs. Abstract: The homeostatic chemokines CCL19 and CCL21 and their common cognate chemokine receptor CCR7 orchestrate immune cell trafficking by eliciting distinct signaling pathways. Here, we demonstrate that human CCR7 is N-glycosylated on 2 specific residues in the N terminus and the third extracellular loop. Conceptually, CCR7 glycosylation adds steric hindrance to the receptor N terminus and extracellular loop 3, acting as a "swinging door" to regulate receptor sensitivity and cell migration. We found that freshly isolated human B cells, as well as expanded T cells, but not naïve T cells, express highly sialylated CCR7. Moreover, we identified that human dendritic cells imprint T cell migration toward CCR7 ligands by secreting enzymes that deglycosylate CCR7, thereby boosting CCR7 signaling on T cells, permitting enhanced T cell locomotion, while simultaneously decreasing receptor endocytosis. In addition, dendritic cells proteolytically convert immobilized CCL21 to a soluble form that is more potent in triggering chemotactic movement and does not desensitize the receptor. Furthermore, we demonstrate that soluble CCL21 functionally resembles neither the CCL19 nor the CCL21 phenotype but acts as a chemokine with unique features. Thus, we advance the concept of dendritic cell-dependent generation of micromilieus and lymph node conditioning by demonstrating a novel layer of CCR7 regulation through CCR7 sialylation. In summary, we demonstrate that leukocyte subsets express distinct patterns of CCR7 sialylation that contribute to receptor signaling and fine-tuning chemotactic responses.